A Rare Scrotal Tumor: Epididymal Cavernous Hemangioma. (6th November 2018) - Karray, Omar; Ben Chehida, Mohamed Ali; Sellami, Ahmed; Mrad Daly, Kheireddine; Mahjoubi, Zied; Zehani, Alia; Ben Rhouma, Sami; Nouira, Yassine
Abstract : Introduction . Paratesticular tumors are rarely observed among scrotal neoplasm. Various types of benign lesions are described. Cavernous hemangioma belongs to uncommon epididymal benign tumors. Clinical and sonographic features are not conclusive and diagnosis requires histological confirmation. Case Presentation . Authors report a case of an epididymal hemangioma in a 56-year-old patient, consulting for a painful scrotal swelling. As malignancy was suspected, he underwent inguinal orchiectomy. Histological examination confirmed the diagnosis of cavernous epididymal hemangioma. Clinical and therapeutic aspects of this rare entity are discussed. Conclusion . Epididymis is an infrequent location of cavernous hemangioma. Diagnosis is rarely made preoperatively as symptoms and radiological aspects are not specific. Conservative surgery must be attempted once feasible for aesthetic and functional purposes.